Study on the influences of RPV deformation on CHF under IVR conditions - Wen, Shuang; Gao, Xinli; Zhang, Rui; Fan, Kebin; Jia, Bin; Jing, Jianping; Liu, Fudong; Tian, Xinlu (Frontiers in Energy Research, 2023)
After the reactor core melt, the thermal impact of high temperature molten mixture to the lower head of reactor pressure vessel (RPV) will cause the shape change of cooling channel constituted by reactor pressure vessel outer surface and other supporting structures. This phenomenon may lead to local heat transfer deterioration and then cause the failure of in-vessel retention (IVR). Therefore, it is necessary to study the reactor pressure vessel deformation under in-vessel retention conditions. This paper proposes a numerical method for the CHF of the outer wall of reactor pressure vessel using ANSYS and FLUENT. The geometry of coolant channel is modeled by ANSYS with the coupling of temperature and mechanical field analysis in ANSYS, and the critical heat flux (CHF) of reactor pressure vessel outer surface is further predicted by FLUENT. With the comparing between test data and calculation, the calculation methods are verified. The results show that the CHF will be decreased by the deformation of PRV caused by the core melt.